A LONGITUDINAL INVESTIGATION OF ENVIRONMENTAL KNOWLEDGE AND PRO-ENVIRONMENTAL BEHAVIOR: MODERATING ROLE OF KNOWLEDGE SHARING KNOWLEDGE HIDING ATTITUDES - Rahayu Puji Suci; Teddy Chandra (Universitas Dharma Wacana, 2022)
The rapidly growing population and modern living standards are causing more and more resource depletion in personal, household, and industrial consumption areas resulting in environmental challenges. Therefore, there is an intense need to investigate the various triggering factors and moderators influencing individuals' pro-environmental behavior and attitudes. Thus, the influence of environmental knowledge on the citizens' pro-environmental behavior has been examined, and the moderating role of knowledge sharing, and knowledge hiding has also been empirically tested. Surveying 582 citizens of Malang, Indonesia, at two different times for six months showed that environmental knowledge is positively and significantly associated with pro-environmental behavior. Moreover, based on the norm’s activation theory, the interactive effect of knowledge sharing with environmental knowledge has been found to enhance pro-environmental behavior. In contrast, results revealed that knowledge hiding when interacting with environmental knowledge of the citizens affects their pro-environmental behavior negatively. Thus, it depicts the negative outcomes of knowledge hiding with multiple managerial and theoretical implications.